2017
DOI: 10.3130/jaabe.16.99
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of User Emotion and Experience in Interaction with Space

Abstract: Designer-oriented space design has been transferred to user-oriented space design that considers users' emotions as well as the functions of the space, producing a multi-sensory space. Further, with the advent of embedded digital media and information technology in a space, various interface functions of the space have been developed and the user experience in the space has been much extended. This research investigated user experience and emotional aspects of a space's design, which have been sparsely researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 21 publications
0
18
0
4
Order By: Relevance
“…Neuroscience and VR can be combined [ 322 ]. This combination allows researchers to develop virtual environments and record the neurophysiological and behavioural responses of experimental subjects [ 323 , 324 , 325 , 326 , 327 , 328 ]. It has been suggested that this combination is more rigorous than research in physical settings using self-reports [ 329 ].…”
Section: Resultsmentioning
confidence: 99%
“…Neuroscience and VR can be combined [ 322 ]. This combination allows researchers to develop virtual environments and record the neurophysiological and behavioural responses of experimental subjects [ 323 , 324 , 325 , 326 , 327 , 328 ]. It has been suggested that this combination is more rigorous than research in physical settings using self-reports [ 329 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cognitive preference related to placeness to be reinforced by place attachment or place identity in the system of thinking. As a result, the relative value of placeness is sometimes evaluated fairly higher from a subjective point of view [15,[40][41][42]. Accordingly, clearer and stronger preference for user-perceived placenessrelated characteristics is associated with relatively higher user utility.…”
Section: Exchange Relationship Between User Utility Value Related To ...mentioning
confidence: 99%
“…La simulación ambiental y la realidad virtual pueden combinarse (Hemeida & Mostafa, 2017;Riva, 2003). Esto permite presentar ambientes mientras se toman los registros neurofisiológicos del usuario (Bohil, Alicea, & Biocca, 2011;Cho & Kim, 2017;Ergan, Radwan, Zou, Tseng, & Han, 2019;Merril, 1997;Radwan & Ergan, 2017). Sinergia que resulta atractiva tanto para la investigación clínica (Tarr & Warren, 2002), como para la arquitectura (Jelić, Tieri, De Matteis, Babiloni, & Vecchiato, 2016).…”
Section: Simulación Ambiental Y Neurociencia Combinadasunclassified
“…Cho & Kim, 2017;Ergan, Radwan, Zou, Tseng, & Han, 2019;Merril, 1997;Radwan & Ergan, 2017). Synergy that is attractive for both clinical research (Tarr & Warren, 2002) and architecture (Jelić, Tieri, De Matteis, Babiloni, & Vecchiato, 2016).…”
Section: Environmental Simulation and Neuroscience Combinedmentioning
confidence: 99%
See 1 more Smart Citation